Transforming study abroad : a handbook - Doerr, Neriko Musha, 1967- (Berghahn Books, 2019)
Written for study abroad practitioners, this book introduces theoretical understandings of key study abroad terms including "the global/national," "culture," "native speaker," "immersion," and "host society." Building theories on these notions with perspectives from cultural anthropology, political science, educational studies, linguistics, and narrative studies, it suggests ways to incorporate them in study abroad practices. Through attention to daily activities via the concept of immersion, it reframes study abroad not as an encounter with cultural others but as an occasion to analyze constructions of "differences" in daily life, backgrounded by structural arrangements.